2008
DOI: 10.1016/j.ibmb.2008.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The invertebrate B0 system transporter, D. melanogaster NAT1, has unique d-amino acid affinity and mediates gut and brain functions

Abstract: The CG3252 gene product, DmNAT1, represents the first Nutrient Amino acid Transporter cloned from Drosophila. It absorbs a broader set of neutral amino acids versus earlier characterized insect NATs and mammalian NATs-B 0 system transporters from the Sodium Neurotransmitter symporter Family (SNF, a.k.a. solute carrier family 6, SLC6). In addition to B 0 -specific L-substrates, DmNAT1 equally or more effectively transports D-amino acids with sub millimolar affinities and 1:1 sodium:amino acid transport stoichio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 40 publications
(65 reference statements)
0
52
0
Order By: Relevance
“…All currently characterized NATs encode transporters with similar electrochemical mechanisms utilizing the most ubiquitous monovalent cation (primarily Na + ) electrochemical gradient to symport (co-transport) neutral amino acids. The NATs population includes broad substrate spectrum, neutral amino acid transporters, which were identified in mammals (Broer et al, 2004) and insects [see figure 1s, B 0 AT1 and DmNAT1, in Miller et al (Miller et al, 2008)]. In insects the NAT subfamily has an additional expansion, which is absent in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…All currently characterized NATs encode transporters with similar electrochemical mechanisms utilizing the most ubiquitous monovalent cation (primarily Na + ) electrochemical gradient to symport (co-transport) neutral amino acids. The NATs population includes broad substrate spectrum, neutral amino acid transporters, which were identified in mammals (Broer et al, 2004) and insects [see figure 1s, B 0 AT1 and DmNAT1, in Miller et al (Miller et al, 2008)]. In insects the NAT subfamily has an additional expansion, which is absent in mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the mammalian transporter families are present in Drosophila, including the facilitative glucose transporters of the GLUT family (60), cationic amino acid transporters (38), ion-dependent and -independent amino acid transporters for neutral amino acids (70,108,117,149), and dipeptide transporters (154). However, intestinal expression has only been reported for the amino acid transporters pathetic, minidiscs, and NAT1 and the dipeptide transporter yin (opt1) (70,117,154), and the roles of these transport systems in the intestine remain to be established. Although many of them may handle dietary nutrients, some may be involved in absorption of fermented and symbiotic products.…”
Section: Absorption Of Carbohydrates and Proteinsmentioning
confidence: 99%
“…Although many of them may handle dietary nutrients, some may be involved in absorption of fermented and symbiotic products. A case in point is the broad neutral amino acid transporter NAT1, which is expressed in the larval posterior midgut and is able to transport both L-and D-isomers of several amino acids (117). D-isomers are particularly abundant in the cell walls of bacteria and can substitute essential L-amino acids in the Drosophila diet (68), suggesting that NAT1 may normally function to absorb substrates from bacteriaenriched fermented diets (16).…”
Section: Absorption Of Carbohydrates and Proteinsmentioning
confidence: 99%
“…The substrate narrowing specializations are far more pronounced for some insect-specific NATs. For example, NAT expansion in mosquitoes is larger than that of mammalian NATs and, in addition to B 0 -like transporters (Boudko et al, 2005a;Miller et al, 2008), includes currently identified Phe-, Trp-and Met-selective members (Meleshkevitch et al, 2006;Meleshkevitch et al, 2009a;Meleshkevitch et al, 2009b). The functional characterization of SNF-5 showed that B 0 -like transporters exist, and are structurally conserved, in free-living nematodes, making them one of the most universal and phylogenetically ancient types of metazoan NATs.…”
Section: Transport Propertiesmentioning
confidence: 99%